THE IMPLEMENTATION OF TEACHING WRITING THROUGH A GENRE-BASED APPROACH - Rahmadhani, Astuti Pratiwi; Afriyanti, Rika; Riza, Armilia (TELL - US JOURNAL, 2022)
This study reports on the effectiveness of teaching writing through a genre-based approach. This study employed a qualitative research design, embracing the characteristics of a case study. The data were obtained from classroom observation. The study involved students at a public high school in Bandung. The result shows that the teaching program of Genre Based Approach which includes Building knowledge of the field (BKOF), Modeling of the text (MOT), Joint construction of the text (JCOT), and Independent construction of the text (ICOT) helped the students to express the idea in writing. It also helped students to understand the language features and structures of the text. Based on the analysis, it is recommended that the teaching program can be applied in various text genres to improve the teaching of English and enhance the students’ writing ability.